Clinical and Epidemiological Characterization of Patients with Rheumatoid Arthritis - Zoe Alina González Otero; Jorge Luis Egüez Mesa; Celestino Fusté Jiménez; Eugenio Alejandro Reyes Medina; José Alberto Borges López; Lázaro Hermes González Otero (Revista Finlay)
Background: rheumatoid arthritis is a chronic systemic inflammatory disease, it has varied clinical manifestations and cause different degrees of discomfort and disability. Objective: to conduct a clinical and epidemiological characterization of all rheumatoid arthritis patients admitted to the clinical services of the Arnaldo Milián Castro Provincial University Hospital. Methods: a cross-sectional study was conducted in the clinical services of the Arnaldo Milián Castro University Hospital from 2009 through 2013. The universe consisted of 280 patients hospitalized due to rheumatoid arthritis. The following variables were studied: age, sex, skin color, past medical history, clinical manifestations, complications, affected organs, time of diagnosis and treatment. Chi square and prevalence ratio with a 95% confidence interval were calculated. Results: arthritis was found in 2 men every 5 women. White middle-aged patients predominated. Hypertension was the major illness described in the past medical history. Arthralgia and movement limitations prevailed. No family history of rheumatic disease was found. The time of diagnosis was less than six months and infection was among the most frequent complications. The most common treatment was the combination of non-steroidal anti-inflammatory drugs and steroids, especially in seropositive patients. Conclusions: rheumatoid arthritis was more common in females and white middle-aged patients. Hypertension was the major illness found in the past medical history. Patients with two target organs affected predominated. Arthralgia and movement limitations prevailed in the clinical picture. The most common treatment was the combination of non-steroidal anti-inflammatory drugs and steroids.